(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
For a long time, play was considered as any activity of a child that does not pursue the goal of obtaining results, carried out for pleasure, "not seriously". In modern psychological and pedagogical science, the terms "play", "play interaction", "play activity" have become quite common scientifically substantiated concepts. Play has ceased to bear the "stigma" of a trifle, fun, entertainment, it is becoming a serious tool of professional activity.